(untitled) (Ustozlar uchun, 2025)
This paper explores the scientific and practical aspects of identifying and classifying innovative products according to the CN FEA system. Rapid technological advancement, increasing prevalence of products with intellectual and multifunctional capabilities, and constantly evolving standardization rules pose new challenges for customs authorities. The study examines difficulties in identifying innovative goods, modern identification methods including expert and laboratory analysis, and the use of databases and AI-assisted classification tools. Special attention is given to Uzbekistan’s current practices and recommendations for improvement. Implemented measures, such as specialized methodological manuals for modular electronic devices, advanced laboratory equipment, and automated risk assessment systems, have significantly enhanced the accuracy, reliability, and efficiency of innovative goods classification. The integration of these scientific and technological approaches demonstrates a model for improving customs operations in line with global standards.